2009
DOI: 10.1007/s10875-009-9341-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Genotype-phenotype Correlation in 62 Patients with X-linked Agammaglobulinemia

Abstract: A critical analysis of the circumstances upon presentation also revealed that under-recognition of recurrent infections and relevant family history are important hurdles to timely diagnosis of XLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
54
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 26 publications
14
54
0
2
Order By: Relevance
“…The finding that mortality rate is variable even within the same PID category is remarkable. This is clearly shown within patients with combined T-and B-cell immunodeficiencies where >85% of patients with RAG1 deficiency died, whereas 45.5% and 16.7% of patients with MHC II deficiency and DOCK8 Owing to the relative rarity of PID patients, multicenter and international collaboration to study outcome and genotypephenotype correlation among patients affected by specific PID disease, as previously performed [11][12][13][14], should be encouraged.…”
Section: Discussionmentioning
confidence: 94%
“…The finding that mortality rate is variable even within the same PID category is remarkable. This is clearly shown within patients with combined T-and B-cell immunodeficiencies where >85% of patients with RAG1 deficiency died, whereas 45.5% and 16.7% of patients with MHC II deficiency and DOCK8 Owing to the relative rarity of PID patients, multicenter and international collaboration to study outcome and genotypephenotype correlation among patients affected by specific PID disease, as previously performed [11][12][13][14], should be encouraged.…”
Section: Discussionmentioning
confidence: 94%
“…TK, pH and SH2 domains were involved in a vast proportion of cases. Lee et al (10) found that patients with missense mutations on average live longer than those with other types of mutations. A study of 110 cases of XLA by Broides et al (11) revealed that 56% of patients with missense mutation were diagnosed at the age of ≥6 years.…”
Section: Discussionmentioning
confidence: 99%
“…While infectious joint inflammation resolving on immunoglobulin replacement therapy is frequently seen in XLA (86), aseptic arthritis has also been described including presentations of RA (87), JIA (88, 89), and enthesitis-related arthritis (ERA) (90). Infiltrating CD8+ T cells can be seen on joint cytology (87).…”
Section: Treatment Of Rheumatologic Disease In Primary Immunodeficmentioning
confidence: 99%